Clinical decision making and outcome in the routine care of people with severe mental illness across Europe (CEDAR). (20th January 2015) - Puschner, B.; Becker, T.; Mayer, B.; Jordan, H.; Maj, M.; Fiorillo, A.; Égerházi, A.; Ivánka, T.; Munk-Jørgensen, P.; Krogsgaard Bording, M.; Rössler, W.; Kawohl, W.; et al.
Abstract : Aims: Shared decision making has been advocated as a means to improve patient-orientation and quality of health care. There is a lack of knowledge on clinical decision making and its relation to outcome in the routine treatment of people with severe mental illness. This study examined preferred and experienced clinical decision making from the perspectives of patients and staff, and how these affect treatment outcome. Methods: "Clinical Decision Making and Outcome in Routine Care for People with Severe Mental Illness" (CEDAR; ISRCTN75841675) is a naturalistic prospective observational study with bimonthly assessments during a 12-month observation period. Between November 2009 and December 2010, adults with severe mental illness were consecutively recruited from caseloads of community mental health services at the six study sites (Ulm, Germany; London, UK; Naples, Italy; Debrecen, Hungary; Aalborg, Denmark; and Zurich, Switzerland). Clinical decision making was assessed using two instruments which both have parallel patient and staff versions: (a) The Clinical Decision Making Style Scale (CDMS) measured preferences for decision making at baseline; and (b) the Clinical Decision Making Involvement and Satisfaction Scale (CDIS) measured involvement and satisfaction with a specific decision at all time points. Primary outcome was patient-rated unmet needs measured with the Camberwell Assessment of Need Short Appraisal Schedule (CANSAS). Mixed-effects multinomial regression was used to examine differences and course over time in involvement in and satisfaction with actual decision making. The effect of clinical decision making on the primary outcome was examined using hierarchical linear modelling controlling for covariates (study centre, patient age, duration of illness, and diagnosis). Analysis were also controlled for nesting of patients within staff. Results: Of 708 individuals approached, 588 adults with severe mental illness (52% female, mean age = 41.7) gave informed consent. Paired staff participants (N = 213) were 61.8% female and 46.0 years old on average. Shared decision making was preferred by patients ( χ 2 = 135.08; p < 0.001) and staff ( χ 2 = 368.17; p < 0.001). Decision making style of staff significantly affected unmet needs over time, with unmet needs decreasing more in patients whose clinicians preferred active to passive (−0.406 unmet needs per two months, p = 0.007) or shared (−0.303 unmet needs per two months, p = 0.015) decision making. Conclusions: Decision making style of staff is a prime candidate for the development of targeted intervention. If proven effective in future trials, this would pave the ground for a shift from shared to active involvement of patients including changes to professional socialization through training in principles of active decision making.